Factors that influence the success of small and medium enterprises in ICT: a case study from the Czech Republic - Strielkowski, Wadim; Krejcí, Martin; Čabelková, Inna (Business: Theory and Practice, 2015)
Small and medium enterprises (SMEs) occupy a large niche in the information and technology sector (ICT) and play an important role in the functioning on any state’s economy. This paper focuses on a specific local market and uses the Czech Republic as a case study in order to establish the success factors crucial for achieving economic success. It aims at determining those factors with the help of econometric success rate models based on the own data collected via the means of questionnaire survey among ICT enterprise. Our results show that the earnings-employee ratio, average revenues and the investment in own R&D play the most important role in the success of Czech SMEs in question. Both, financial and non-financial indicators perform significantly in the predictions of success.